Troubling gendered umbrellas: engaging complexity within legacies of leisure research. Issue 3 (3rd July 2019) - Flanagan, Ashley K.
ABSTRACT: What do umbrellas have to do with leisure research? Why do they need to be troubled? Throughout the course of this manuscript, we will unpack understandings of umbrella categories – specifically, gendered umbrella categories – and why it is relevant for leisure scholars to consider these categories within their research practices. Following a discussion of the complexity involved in projects of representation, leisure scholars will find a number of guiding principles and questions that highlight the importance of doing research in ways that are simultaneously aware of but also trouble the influence of taken for granted gendered umbrellas within research processes. By thoughtfully considering the way we as leisure researchers engage in research, we can open up space within our research for the legacies that do not fit neatly into binarized identity categorisations – as well as create more opportunities for doing leisure research in increasingly socially just ways.